Performance Evaluation of fiber optic communication Using Boolean Function Approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper a mathematical model has been formulated to assess reliability of a fiber optic communication system using Boolean algebra technique. This technique is simple and convenient than other methods when there are more complexities in a system. The model has been solved and some special cases have been considered to evaluate different reliability parameters. A comparison of decline in reliability with respect to time has been made under those special cases. Another comparison of decrease in MTTF with increase in failure rate has been done.